The effect of Blended Learning Model on students’ Writing Skill: n Experiment Study at Tenth Grade of Madrasah Aliyah Ibnu Husain Surabaya - juniati; Khoirul Huda (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
this research aims to know the effect of the Blended Learning method on students' writing achievement in the description text. This study used a quasi-experimental in whichdesign involves two groups, namely the experimental group and the control group. Theexperimental group was given learning using the flipped classroom model, and the controlgroup was given learning using an online driver or Enriched – Virtual model. The resultshows that students who are taught using conventional methods can be proven from theaverage writing ability. Students taught using the Flipped Classroom model (86,96) havehigher scores than those taught using the Online Driver model (81,8). Furthermore, based onthe results of the T-test, it appears that sig. (0.177) > 0.05. It means that this research indicatesan effective Flipped Classroom model